2014
DOI: 10.18632/oncotarget.2722
|View full text |Cite
|
Sign up to set email alerts
|

The inverse relationship between bladder and liver in 4-aminobiphenyl-induced DNA damage

Abstract: Bladder cancer risk is significantly higher in men than in women. 4-Aminobiphenyl (ABP) is a major human bladder carcinogen from tobacco smoke and other sources. In mice, male bladder is more susceptible to ABP-induced carcinogenesis than female bladder, but ABP is more carcinogenic in the livers of female mice than of male mice. Here, we show that castration causes male mice to acquire female phenotype regarding susceptibility of bladder and liver to ABP. However, spaying has little impact on organ susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…Similar results were shown in BALB/c mice and C57BL/6 mice. 13,15 Sult1a1 KO caused marked decrease in liver dG-C8-ABP level, decreasing 21.2-to 21.4-fold (male-female) in the single ABP treatment and 51.7-to 52.2-fold (malefemale) in the 7-day treatment with ABP ( Figure 2C,D). Thus, Sult1a1 is the critical ABP activator in liver.…”
Section: Ko Of Sult1a1 and Sult1d1 Protects Liver Against Abp And Ementioning
confidence: 95%
See 1 more Smart Citation
“…Similar results were shown in BALB/c mice and C57BL/6 mice. 13,15 Sult1a1 KO caused marked decrease in liver dG-C8-ABP level, decreasing 21.2-to 21.4-fold (male-female) in the single ABP treatment and 51.7-to 52.2-fold (malefemale) in the 7-day treatment with ABP ( Figure 2C,D). Thus, Sult1a1 is the critical ABP activator in liver.…”
Section: Ko Of Sult1a1 and Sult1d1 Protects Liver Against Abp And Ementioning
confidence: 95%
“…Liver UGT catalyzes the conjugation of aromatic amines with glucuronic acid; the conjugates are excreted in the urine and are labile, delivering carcinogenic metabolites to the bladder . Indeed, we showed that transgenic mice with liver expression of an ABP‐metabolizing human UGT have increased dG‐C8‐ABP level in the bladder following exposure to ABP . However, in wild‐type (WT) mice (C57BL/6), liver ABP‐specific UGT activity is significantly higher in female mice than in male mice, and in castrated male mice, liver UGT activity is similar to that in female mice .…”
Section: Introductionmentioning
confidence: 93%
“…While the approach also relies on the use of nanoflow LC, in addition, it incorporates on-line sample cleanup procedures that bypass much of the typical manual sample processing to reduce sample losses. This approach has been more recently employed in the analysis of 4-aminobiphenyl DNA adducts in bladder and liver tissues [22]…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the same group found the inverse relationship between bladder and liver in 4-ABP induced DNA damage by showing that in mice, male bladder is more susceptible to ABP-induced carcinogenesis than female bladder and the situation is completely reversed in liver (as shown in Figure 34). They suggested that androgen may play a key role in this gender disparity by down-regulating some metabolic enzymes which activate ABP in the liver [109]. Ongoing studies in our laboratories suggest that sulfotransferase enzymes which catalyze the sulfation of 4-ABP may play key role in mediating the gender disparity described above.…”
Section: Investigation Of 4-abp Induced Bladder Cancermentioning
confidence: 79%
“…Bladder cancer is one of the major cancers associated with 4-ABP, and it has been studied for many years in Vouros' group in a collaboration with Zhang's group [6,17,72,109]. Two major research directions have been undergoing in both laboratories: one is to understand the role of 4-ABP in the development of bladder cancer; another is to develop prevention strategies for bladder cancer.…”
Section: Investigation Of 4-abp Induced Bladder Cancermentioning
confidence: 99%